(untitled) (World Economics and Finance Bulletin, 2024)
This research mainly aims to show the effect of using material flow accounting on costs reduction and competitive advantage support in industrial companies, by costs reduction through the optimal use of resources, and showing the effect of this reduction in competitive advantage support, to achieve the objective of this research, the study followed the inductive and deductive approach through a case study in Basra Asphalt Plant. The laboratory data was adopted to clarify the research problem and to achieve its objective and hypothesis to determine the effect of material flow costs accounting in the competitive advantage support of the plant